2020
DOI: 10.1039/c9ra10483f
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study on the excited states of pyrene and its derivatives using multi-reference perturbation theory methods

Abstract: The excited states of phenyl-substituted pyrene derivatives were calculated using multi-reference perturbation theory methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 131 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…The analysis is now extended to the larger molecule pyrene. The excited states of pyrene have been studied in earlier work using multiconfigurational wave function-based methods and TDDFT [33,34,36,43] and the vibrational resolved spectra for the lowest allowed transition (1B 3u ) have been reported [42,43]. The computed vertical excitation energies along with a description of the transition in terms of the molecular orbitals, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis is now extended to the larger molecule pyrene. The excited states of pyrene have been studied in earlier work using multiconfigurational wave function-based methods and TDDFT [33,34,36,43] and the vibrational resolved spectra for the lowest allowed transition (1B 3u ) have been reported [42,43]. The computed vertical excitation energies along with a description of the transition in terms of the molecular orbitals, shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the challenge of predicting the vertical excitation energies with sufficient accuracy that allows direct comparison with experimental spectra that involve contributions from a range of electronic transitions. Multiconfigurational wave function-based methods have considered the lowest two energy states (1B 2u and 1B 3u ) [33,34], so while they predict accurate values for these states, their performance for the higher-energy states has not been established. Figure 7 shows a comparison between the experimental spectrum and the calculated spectrum using the FCHT approximation that incorporates the lowest two energy allowed transitions and the bond lengths for the different excited states are shown in Figure S4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they observed that the dyeing effect of the pyrene derivative is more sensitive and stronger than that of pyrene. Because of its characteristic photophysical behavior such as its prominent and typical absorption bands and uorescence emission, 25,26 pyrene was involved in numerous supramolecular studies. The rst two excited states of pyrene compounds, 1La and 1Lb, p / p*, corresponding to S 0 / S 1 and S 0 / S 2 excitations, proved to have the main role in the photophysical processes involving such molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…The rst two excited states of pyrene compounds, 1La and 1Lb, p / p*, corresponding to S 0 / S 1 and S 0 / S 2 excitations, proved to have the main role in the photophysical processes involving such molecular systems. 25,[27][28][29][30] The band's intensity variation (including their appearance or disappearance), together with the wavelength shis in UV-vis and uorescence spectra varies from one pyrene derivative to another. The studies indicate that pyrene compounds are able to form dimers (by the weak association in the ground state), excimers (by the strong association in the excited states), and/or p-p stacking aggregates.…”
Section: Introductionmentioning
confidence: 99%